Educação e transcendência : dimensões contempláveis, aspectos edificáveis, categorias compartilháveis - Schock, Marlon Leandro (2008)
The present dissertation is a study about the human transcendence. It broaches the cultural/ontological character of the transcendence and its apprehension and manifestation through ponderable dimensions, of constructible aspects and sharing categories. Starting from the elements which the author calls "transcendence means", it aims, having as main speaker Paulo Freire, tracing some relations of the transcendence with the education. Throughout the work it aims answering some questions about the transcendence theme in relation to the education. In the first chapter it broaches the most central question of the investigation: the human being as a being of transcendence. In this discussion were included the consequent questions of transcendence as ontology or cultural process and the essential and dynamical relation between human transcendence and immanence too. Along the investigation it was shown to be necessary an analogy between the terms transcendence and sacred, noticed that this second one demonstrated to hold meaning similarities, and therefore, it became analysis subject for possible distinction and in order to trace probable affinity points. In the second chapter, having the pedagogue Paulo Freire as a reference for this dialogue the author intends answering the questions related to the education and its relation with the human transcendence ability more specifically. Starting from this slant it investigates in Freire the transcendence means that find their matches enlisted in the first chapter, viewpoint from which the reflection about the function of the education in relation to the incompleteness, to the human amplitude and inquietude start.